Violencia en las relaciones románticas y tipología familiar en jóvenes universitarios (2021)
Dating violence during youth transforms into a social problem of great importance because of the impact and consequences for life, including being a strong predictor of violence in adult life. The aim of the present study was to identify the relationship between violent dating behavior, family typology and some sociodemographic factors in a sample of university students. A descriptive-correlational cross-sectional quantitative study was carried out for a sample of 515 university students from five higher education institutions in the city of Bogotá D.C., aged between 18 and 25 years. Among the findings, for the study sample, relationships were found between these factors of violence and some family typologies and the factors sex and socioeconomic level.